Managing in Soviet Georgia: an extreme example in comparative management. (31st January 2008) - Mars, Gerald; Altman, Yochanan
This historical reflection of an important period of the 20th century – the vagaries of the Soviet-type command economy, accords us the opportunity to discuss the practice and art of management as an ongoing negotiation between different agencies, interest groups, constraints and opportunities. We detail the case of Soviet Georgia's hidden economy, mediated as it was through locally based personal support networks and illustrating our arguments with a case study of legal/illegal manufacturing enterprise. We conclude with a note on present-day Central-Eastern European economies and a commentary on implications for management in liberal economies as they become more globally integrated.